2009
DOI: 10.1007/s00702-009-0356-0
|View full text |Cite
|
Sign up to set email alerts
|

1 Hz rTMS preconditioned by tDCS over the primary motor cortex in Parkinson’s disease: effects on bradykinesia of arm and hand

Abstract: To investigate whether a period of 1 Hz repetitive transcranial magnetic stimulation (rTMS) over M1 preconditioned by tDCS improves bradykinesia of the upper limb in Parkinson's disease (PD). Fifteen patients with PD performed index finger, hand tapping and horizontal pointing movements as well as reach-to-grasp movements with either hand before (baseline conditions) and after a period of 1 Hz rTMS preconditioned by (1) sham, (2) anodal or (3) cathodal tDCS over the primary motor cortex contralateral to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…Boggio et al (2006) demonstrated that patients with PD performed better in a memory and alertness test during a left prefrontal tDCS than during sham-stimulation. In another study the technique of rTMS was combined with tDCS in order to improve bradykinesia in PD (Grüner et al, 2010). In this study low frequency rTMS over the primary motor cortex contralateral to the more effected upper extremity was preceded by either sham, cathodal or anodal tDCS.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…Boggio et al (2006) demonstrated that patients with PD performed better in a memory and alertness test during a left prefrontal tDCS than during sham-stimulation. In another study the technique of rTMS was combined with tDCS in order to improve bradykinesia in PD (Grüner et al, 2010). In this study low frequency rTMS over the primary motor cortex contralateral to the more effected upper extremity was preceded by either sham, cathodal or anodal tDCS.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…Similar to Lefaucheur's comprehensive review, 8 we chose to exclude three studies that used tDCS as a priming mechanism for testing an alternative intervention, namely rTMS. [9][10][11] tDCS tDCS involves the delivery of a low-intensity current (1-2 mA) using relatively large electrodes (~2-10 cm) generally placed on the scalp. Most studies of tDCS employ a " bipolar" montage consisting of one anode and one cathode to induce an electric field that passes across the various cranial structures (skin, bone, pia, and cerebrospinal fluid) to reach the brain parenchyma.…”
Section: Search Strategymentioning
confidence: 99%
“…Cathodal tDCS interferes with beneficial effects of 1 Hz rTMS in finger tapping and pointing movements (Gruner et al, 2010), but anodal stimulation does not. Grasping cannot be modulated by tDCSprimed 1 Hz rTMS (Eggers, Gruner, Ameli, Sarfeld, & Nowak, 2012), and anodal tDCS, but not cathodal stimulation, with subsequent 1 Hz rTMS improves gait (von Papen, Fisse, Sarfeld, Fink, & Nowak, 2014).…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%